Study Of Local Potential-Based Creative Economy For Community Empowerment - Agus Lukman Hakim; Rahmat Maulana; Robin; M. Robbi Qawi; Nopi Andayani; Firdaus, Siti Aina (MIMBAR : Jurnal Sosial dan Pembangunan, 2024)
The study examines local potential-based creative economics to empower the community. The purpose of this study is to analyze the development of creative economies based on local potential in Serang, the potential of a creative economy based on the local potential of Serang as well as to formulate strategies for the development of creativity based on regional potential to empower the community in Serang. (financial, human resources, technology, industry, and institutions). Out of the analysis of the five main pillars of creative economy support in the Serang, the financial pillars have the highest value, while the industry pillar has the lowest value. Developing creative economic activity requires strong intervention against the pillars of industry, institutional, and technological intervention.